PENERAPAN MODEL PEMBELAJARAN KOOPERATIFTIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI SD NEGERI 006 TRI MULYA JAYA KECAMATAN UKUI - Setyaningsih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low science learning outcomes of sixth-grade students at SD Negeri 006 Tri Mulya Jaya. Of the 20 students, only 10 students achieved mastery learning. The low learning outcomes were caused by several factors, namely: (a) the learning model used by the teacher was conventional, and (b) the learning process was teacher-centered, resulting in passive students. The purpose of this study was to improve students’ science learning outcomes through the implementation of the cooperative learning model Make a Match. This study was conducted using classroom action research consisting of two cycles. The data collected included teacher activity, student activity, and students’ science learning outcomes. The results showed that both learning activities and science learning outcomes improved in each cycle. Student activity increased from an average of 54.00% at the first meeting of Cycle I to 62.00% at the second meeting of Cycle I. In Cycle II, student activity further increased to 75.00% at the first meeting and 83.00% at the second meeting. In terms of learning outcomes, the percentage of students achieving mastery learning increased from 50.00% with an average score of 61 in the preliminary data to 75.00% with an average score of 79 in Cycle I, and further increased to 85.00% with an average score of 76.5 in Cycle II. Based on these results, it can be concluded that the application of the Make a Match cooperative learning model can improve science learning outcomes of sixth-grade students at SD Negeri 006 Tri Mulya Jaya.